THE RELATIONSHIP BETWEEN EATING HABITS AND PHYSICAL ACTIVITY WITH OVERWEIGHT INCIDENCE AMONG PUBLIC HEALTH STUDENTS AT FACULTY OF PUBLIC HEALTH, NUSA CENDANA UNIVERSITY, KUPANG CITY, INDONESIA IN 2025 - Wahyuni , Maria Magdalena Dwi; Hinga, Indriati Andolita Tedju; Werang, Raymundus Ratu; Banuanek, Yohanis; Lay, Setyaputri; Manuk, Asti; Leba, Nelsi djara; Winda, Winda (JURNAL WIDYA MEDIKA, 2025)
University students' nutritional status serves as a vital indicator for evaluating human resource quality in higher education. Despite their knowledge in nutrition and health, public health students are not immune to overweight risks due to lifestyle changes during college life. This study analyzed the relationship between eating habits and physical activity with overweight incidence among public health students at Faculty of Public Health, Nusa Cendana University. A cross-sectional study was conducted in March-April 2025 involving 210 students selected through cluster random sampling. Data were collected using validated questionnaires and analyzed using chi-square tests with 95% confidence interval. The study found significant relationships between eating habits and overweight incidence (p=0.041<0.05) and between physical activity and overweight incidence (p=0.041<0.05). Among students with good eating habits, 27.4% were overweight, while 25.8% of those with poor eating habits were overweight. For physical activity, 19.7% of students with good physical activity levels were overweight compared to 35.5% with poor physical activity levels. Both eating habits and physical activity significantly influence overweight incidence among public health students, highlighting the need for integrated health promotion programs.